2016
DOI: 10.14453/aabfj.v10i3.2
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Financial Risk Tolerance on Investment Decision-Making in a Financial Advice Context

Abstract: Client risk tolerance is universally assessed in the advisory process to help financial advisers provide suitable advice that assists clients in their investment decision-making. Although there is a well-established literature on risk tolerance and decision-making, little is known about financial risk tolerance and its influence on investor decisions in the financial advice context. Thus, the purpose of this study is to examine this influence with a focus on the key expected risk tolerance determinants: client… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 42 publications
5
24
0
3
Order By: Relevance
“…Previous research is consistent in concluding that individuals with better financial understanding, experience, and knowledge will lead them to have a higher risk tolerance than others. Similar results are tracked in Christina (2019), Fernandes et al (2014), Loke (2015), Nguyen et al (2016), Samsuri et al (2019) and Wisudanto and Zidni (2016) found that improving the understanding of the financial product is a critical component to make the correct and right option in regard to financial decision making. In general, better educated men were found to have higher financial risk tolerance from a study in Pakistan .…”
Section: Financial Knowledgesupporting
confidence: 56%
See 2 more Smart Citations
“…Previous research is consistent in concluding that individuals with better financial understanding, experience, and knowledge will lead them to have a higher risk tolerance than others. Similar results are tracked in Christina (2019), Fernandes et al (2014), Loke (2015), Nguyen et al (2016), Samsuri et al (2019) and Wisudanto and Zidni (2016) found that improving the understanding of the financial product is a critical component to make the correct and right option in regard to financial decision making. In general, better educated men were found to have higher financial risk tolerance from a study in Pakistan .…”
Section: Financial Knowledgesupporting
confidence: 56%
“…For those older Malaysians retire with insufficient savings, it may motivate them to take higher risk and seek for investment with higher returns. As a result, financial risk tolerance has been a prominent study in issues related to financial management, investment and investor's investment decisions (Nguyen et al, 2016;Chng & Hafinaz, 2019;Kanagasabai & Aggarwal, 2020). Many studies have cited and defined financial risk tolerance as the maximum degree of uncertainty of an individual's willingness to accept risk or uncertainties when he or she is making a decision (Roszkowski & Grable, 2010;Nobre et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of financial literacy on risk tolerance has been researched in a relatively smaller number of studies. In these studies, it was generally identified that there was a positive relationship between financial literacy/ financial education level and financial risk tolerance (e.g., Bajo et al, 2015;Bayrakdaroğlu & Kuyu, 2018;Grable, 2000;Grable & Joo, 1999Masters, 1989;Nguyen et al, 2016;Wang, 2009). Masters (1989) analyzed the risk tolerance and investment knowledge for a sample of 480 investors in a Midwestern investment firm through covariance analysis and established that those with knowledge about investment had higher risk-taking tendencies than those with no or less knowledge about investment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This issue of AABFJ begins with Nguyen, Gallery and Newton (2016) as they examine the influence of risk tolerance on investment decision making. They also discuss a new theoretical model more determining risk tolerance in financial planning clients and report on their results when testing this model in an Australian context.…”
mentioning
confidence: 99%